The Relationship between Skin Conductance and Upright Stance Body Sway in Healthy Young Subjects: SCL AND BODY SWAY - Yilmaz, Alpaslan (Progress in Nutrition, 2021)
Study Objectives: State anxiety and arousal levels are known to affect skin conductance level, spontaneous fluctuations of skin conductance, and postural control. In this study, we aimed to investigate whether skin conductance level and spontaneous fluctuations of skin conductance are associated with postural sway. Methods: Skin conductance and postural sway were continuously recorded for two minutes from 25 male participants aged 19 to 25. Skin conductance was recorded from the palmar surface of the third and fourth fingers of the non-dominant hands of the participants. A force platform sized of 40x40cm was used to determine postural sway. Results: No correlations were found between the number of spontaneous fluctuations number and any of body sway parameters. Our results indicated a linear relationship between the skin conductance and i) the root-mean-square of the body sway in the anteroposterior axis (r=0.486, p<0.05) and ii) the center of pressure sway area (r=0.519, p<0.05). Conclusion: Our findings pointed out that increased skin conductance level leads imply a cause effect relationship is associated with increased body sway in anteroposterior axis and increased body sway area.